EARLY CHILDHOOD EDUCATION PRINCIPALS' STRATEGIES IN IMPLEMENTING TRANSFORMATIONAL LEADERSHIP TO EMPOWER TEACHERS IN AN ERA OF CHANGE - Iwan Perdana; Yuliana Nurhayati (Bajang Institute, 2026)
This study intends to explore the subjective experiences of school principals in implementing transformational leadership to empower Early Childhood Education (PAUD) teachers. A phenomenological approach is utilised to understand the essential meaning of the experience. Data were acquired through in-depth interviews with four PAUD principals and were evaluated thematically. The findings of the study reveal three main themes, namely (1) Leadership as Inspiration and Exemplary in an Empowering Space, (2) Mentoring Strategies through Communication, Mentoring, and Appreciation to Fight Resistance, and (3) Leadership Success through Changing the